On the remainder terms of the asymptotic expansions of the characteristic functions and their derivates - Bikelis, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Бикялис. Об остаточных членах в асимптотических разложениях для характеристических функций и их производныхA. Bikelis. Apie charakteringų funkcijų ir jų išvestinių asimptotinių išdėstymų liekamuosius narius